Are we all the same or are we all different? : Scenic practices stimulating the debate about the difference in the school environment (DAPesquisa, 2021)
The contemporary society have many standards to be followed: aesthetic, forms to think, forms to act. People that doesn’t follow this standards, many time are seen how undocked (BERSELLI; ISAACSSON, 2018) and the school environment is one of the places where the standards are more reinforced: students in a row, learning the same contents, seeking the same notes and they can’t dialogue. Scenic practices that go against the dominant discourse (FORTIN, 2011), are seen here as possible strengthens of debates about differences, promoting a review of understandings about disability and ability by put people in the focus of their own research based on practices experiences. Being that enhancers are so big, they can be in the school environment since the beginning’s years, affording practices and experiences that showing the singularities of everyone and the respect with everybody.
Keywords: Drama in education; Children with disabilities-Education-Art, [etc.]; School environment; Prejudices